2019
DOI: 10.1111/plb.13020
|View full text |Cite
|
Sign up to set email alerts
|

Presence of the anther gland is a key feature in pollination of the early‐branching papilionoidsDipteryx alataandPterodon pubescens(Leguminosae)

Abstract: The presence of glandular appendages in the anthers is a rare condition in angiosperms. In Leguminosae it occurs in species of the Mimosoid clade and in earlybranching clades of papilionoids such as Dipterygeae. In Dipterygeae such appendages surprisingly exhibit a secretory cavity instead of secretory emergences as is the case for the Mimosoid clade. Thus, the objective of this study was to elucidate the function of anther glands in Dipteryx alata and Pterodon pubescens, species in the Dipterygeae clade that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Previous studies have reported that the epithelium and parenchymatous sheath act as secretion production sites (Rodrigues et al, 2011a,b;Leite et al, 2014;Palermo et al, 2018). The ultrastructure of epithelial cells shows that the secretion is externalized to the lumen by the eccrine mechanism, corroborating the study of Leite et al (2019). The presence of numerous vesicles showing the path of cell secretion towards the lumen, fusion of vesicles and the accumulation of secretions in the periplasmic space of epithelial cells is a strong indication of a granulocrine secretory process (Franco & Albiero 2018;Almeida & Paiva 2019).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Previous studies have reported that the epithelium and parenchymatous sheath act as secretion production sites (Rodrigues et al, 2011a,b;Leite et al, 2014;Palermo et al, 2018). The ultrastructure of epithelial cells shows that the secretion is externalized to the lumen by the eccrine mechanism, corroborating the study of Leite et al (2019). The presence of numerous vesicles showing the path of cell secretion towards the lumen, fusion of vesicles and the accumulation of secretions in the periplasmic space of epithelial cells is a strong indication of a granulocrine secretory process (Franco & Albiero 2018;Almeida & Paiva 2019).…”
Section: Discussionsupporting
confidence: 77%
“…Epithelial cells with thin, disorganized walls, a winding plasma membrane, vacuolization, low-density peripheral cytoplasm with little osmiophilic material, few organelles and mitochondria and numerous vesicles adhered to the membrane are evidence that secretory cells do not present an intense secretory process, as observed in duct and cavity-secreting epithelial cells in the literature (Franco & Albiero 2018;Palermo et al, 2018;Leite et al, 2019;Haratym et al, 2020). However, our results corroborate Peng et al (2012) and Turner & Lange (2015) when describing ultrastructural characteristics of cavities in adult tissue, and in part with results of Lacchia & Carmello-Guerreiro (2009) for epithelial cells of secretory ducts of Anacardiaceae in the senescent stage.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Gland-secreted secondary metabolic compounds such as aromatic compounds, essential oils or floral volatile scents act directly on the attraction of pollinators or defense against herbivory [9][10][11][12][13]. Several functions of anther glands have also been reported, such as containing adherent substances to aggregate pollen grains and attach them to the pollinator body [14][15][16][17][18], being rewarded as food to the pollinator, and containing substances for defense against phytophagous insects [15]. Moreover, floral stomata may act in the exudation of nectar [19,20] or emission of volatile organic compounds [21,22].…”
Section: Introductionmentioning
confidence: 99%